LOGICAL THINKING IN THE PROCESS OF TEACHING GEOMETRY TO FUTURE ENGINEERS - Mamurova Feruza Islomovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. Descriptive geometry explores practical problems, being a means to move from the qualitative study of phenomena to the study of quantitative patterns. Computer technology has taken on many computational responsibilities, but this does not mean that it is not necessary to develop geometric thinking and the ability to apply geometric methods in solving technical problems.